k-4=-11

Simple and best practice solution for k-4=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for k-4=-11 equation:


Simplifying
k + -4 = -11

Reorder the terms:
-4 + k = -11

Solving
-4 + k = -11

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + k = -11 + 4

Combine like terms: -4 + 4 = 0
0 + k = -11 + 4
k = -11 + 4

Combine like terms: -11 + 4 = -7
k = -7

Simplifying
k = -7

See similar equations:

| -4=6+v | | 20=x/26 | | -9+x=5 | | t(n)=3+6n | | 8y-12=2(4y-6) | | 12x-2(x-4)+7=35 | | -3=k-19 | | 0.08+3=3.8 | | 2x^3-3p=8 | | -28x+12=-32 | | -28=n+(-17) | | 8x-4-(-x-7)+9x+6=12x-7 | | 5y+2+5y+2+4y+4y=166 | | [x]=n | | 5p+6q-4(8p-4q)= | | 3(20+w)=81 | | 3(x+2)-5(4x-4)=0 | | 2x-1y=-1 | | 2k^2=18 | | Whatdoes(y)= | | 8z=155 | | 2x^2-3=10 | | -2-6n=4n+4(n-4) | | -3m+5(m+1)=11 | | 3y-6=29-3y | | 4x+1+7x+3=180 | | 1/2(x+5)-4=1/3(2x-1) | | 7y+2(y-3)=-31 | | 5(y-4)=3(y+2) | | .25y+.66666666666=.75y-.16666666666 | | 2(3x-2)-(2x-3)=15 | | 5(2-x)=2x(x-2) |

Equations solver categories